The Political Orientation of Extra-Campus Student Organizations in the 2019 Presidential Election - Syahrul, Fathullah; Paskarina, Caroline; Sumadinata, R Widya Setiabudi (Society, 2020)
This research aims to analyze extra-campus student organizations' political orientation in the 2019 presidential election in Makassar city using the qualitative descriptive research methods approach. Data collection methods use in-depth interviews and literature studies. Informants selection using purposive sampling techniques. This research indicates that internal factors relate to the extra-campus student organization's internal conditions in the 2019 presidential election in Makassar city. These internal conditions include encouraging their cadres to mature politically and democratically, maintaining the neutrality and idealism of cadres, and keeping the nation and state integrity. Besides, they supervise the government by conducting dialogue and discussion. At the same time, they imply that the 2019 presidential election's political agenda is a learning arena and rejects practical politics and oversees the candidate's vision and mission and every government policy by conducting studies. External factors are related to the influence from outside the extra-campus student organization, namely the alumni organization. The eight extra-campus student organizations consisting of HMI, PMKRI, GMKI, GMNI, PMII, IMM, KAMMI, and GEMA Pembebasan stated no intervention to select one candidate pair in the 2019 presidential election in Makassar city based on alumni's organizational instructions. There are three political orientations in the extra-campus student organizations in Makassar city: first, cognitive political orientation, second, affective political orientation, and third, evaluative political orientation.